Interaction of polymorphism of the interleukin-6 gene with immunological damages and their role in the development of mixed cryoglobulinemia in patients with chronic hepatitis C - Kalashnyk, K. V.; Riabokon, Yu. Yu.; Riabokon, O. V.; Калашник, Кирило Вадимович; Рябоконь, Юрій Юрійович; Рябоконь, Олена Вячеславівна; Калашник, К. В.; Рябоконь, Ю. Ю.; Рябоконь, Е. В. (Запорізький державний медичний університет, 2019)
Aim. To determine the role of the relationship of immunological disorders with interleukin-6 gene polymorphism in the formation of HCV-associated mixed cryoglobulinemia. Materials and methods. The study included 149 patients with chronic hepatitis C. The polymorphism of the IL-6 gene (rs1800795) was determined by the method of polymerase chain reaction, the quantitative content of IL-6, RF IgM and IgG by enzyme immunoassay, cryoglobulins by spectrophotometric method. The patients were divided into groups depending on the polymorphism of the IL-6 gene and the presence of mixed cryoglobulinemia. Results. The frequency of formation of HCV-associated mixed cryoglobulinemia depended on the polymorphism of the IL-6 gene. In patients with chronic hepatitis C with mixed cryoglobulinemia, the frequency of registration of the CC genotype of the IL-6 gene was lower than in patients without mixed cryoglobulinemia, namely, in 9.7 % versus 28.6 % of patients. The presence of the G-allele, namely the CG/GG genotypes of the IL-6 gene polymorphism, was more often detected in patients with mixed cryoglobulinemia, namely, in 90.3 % of patients against 71.4 % of patients without signs of mixed cryoglobulinemia (χ2 = 8.94, P = 0.003). In the presence of G-allele, the quantitative content of IL-6 in the serum of the general group of patients with CHC was higher than in healthy people (P < 0.01), and in the presence of the genotype, the CC did not differ from the control group (P > 0.05). The highest levels of IL-6 were recorded in patients with HCV-associated mixed cryoglobulinemia who had the G-allele. The content of IL-6 in the blood serum of these patients exceeded the indicators of both healthy people (P < 0.001) and the results of patients without mixed cryoglobulinemia (P < 0.01). In patients with chronic hepatitis C with mixed cryoglobulinemia, even in the presence of the CC genotype, the content of IL-6 in serum was higher both in comparison with healthy (P < 0.01) and in comparison with patients without signs of this extrahepatic manifestation (P < 0.01). In patients with chronic hepatitis C with mixed cryoglobulinemia, the presence of CG/GG genotypes was associated not only with the highest serum IL-6 content, but also with the presence of more pronounced autoimmune disorders due to a higher content of RF IgM (P = 0.04) and mixed cryoglobulins (P = 0.03) in serum, in comparison with patients who had the CC genotype. Moreover, the presence of more pronounced immune disorders in patients with HCV-associated mixed cryoglobu¬linemia in the presence of CG/GG genotypes was accompanied by more frequent manifestation of severe general weakness (P = 0.003), arthralgia (P = 0.02) and the formation of Meltzer’s triad. Conclusion. The frequency of detection of the G-allele, namely the CG/GG genotypes of the IL-6 gene polymorphism, is the highest in patients with HCV-associated mixed cryoglobulinemia (90.3 %). The presence of CG/GG genotypes in patients with chronic hepatitis C with mixed cryoglobulinemia contributes to more pronounced immunological disorders due to the highest content of IL-6, mixed cryoglobulins, and RF IgM in serum, which causes the manifestation of the clinical symptoms of this hepatic manifestation. Мета роботи – визначити роль взаємозв’язків імунологічних порушень із поліморфізмом гена інтерлейкіну-6 у формуванні HCV-асоційованої змішаної кріоглобулінемії. Матеріали та методи. У дослідження залучили 149 пацієнтів із хронічним гепатитом С (ХГС). Визначили поліморфізм гена ІЛ-6 (rs1800795) методом полімеразної ланцюгової реакції, кількісний вміст ІЛ-6, RFIgM та IgG методом імуноферментного аналізу та змішаних кріоглобулінів спектрофотометричним методом. Пацієнтів поділили на групи залежно від поліморфізму гена ІЛ-6 і наявності змішаної кріоглобулінемії. Результати. Встановили, що частота формування HCV-асоційованої змішаної кріоглобулінемії залежала від поліморфізму гена ІЛ-6. У хворих на ХГС зі змішаною кріоглобулінемією частота реєстрації генотипу CC гена ІЛ-6 була меншою, ніж у пацієнтів без змішаної кріоглобулінемії – у 9,7 % проти 28,6 % хворих. Наявність G-алеля, а саме генотипів CG/ GG поліморфізму гена ІЛ-6, частіше визначали у хворих зі змішаною кріоглобулінемією – у 90,3 % проти 71,4 % хворих без ознак змішаної кріоглобулінемії (χ2 = 8,94, р = 0,003). За наявності G-алеля кількісний вміст ІЛ-6 у сироватці крові загальної групи пацієнтів із ХГС був вищим, ніж у здорових осіб (р < 0,01), а за наявності генотипу СС не відрізнявся від показника осіб контрольної групи (р > 0,05). Найвищий рівень вмісту ІЛ-6 зафіксували в пацієнтів із HCV-асоційованою змішаною кріоглобулінемією, які мали G-алель. Вміст ІЛ-6 у сироватці крові цих хворих перевищував показники як здорових осіб (р < 0,001), так і пацієнтів без змішаної кріоглобулінемії (р < 0,01). У хворих на ХГС зі змішаною кріоглобулінемією навіть за наявності СС-генотипу вміст ІЛ-6 у сироватці крові був вищим порівняно зі здоровими (р < 0,01) і хворими без ознак цього позапечінкового прояву (р < 0,01). У хворих на ХГС зі змішаною кріоглобулінемією наявність генотипів CG/GG асоціювалася не тільки з найвищим вмістом ІЛ-6 у сироватці крові, але і з вираженішими автоімунними порушеннями внаслідок вищого вмісту RF IgM (р = 0,04) та змішаних кріоглобулінів (р = 0,03) у сироватці крові порівняно з пацієнтами, які мали генотип CC. Більш виражені імунні порушення у хворих із HCV-асоційованою змішаною кріоглобулінемією за наявності генотипів CG/GG супроводжувалися частішою маніфестацією вираженої загальної слабкості (р = 0,003), артралгій (р = 0,02) та формуванням тріади Мельтцера. Висновки. Частота виявлення G-алеля – генотипів CG/GG поліморфізму гена ІЛ-6 – є найвищою у хворих із HCV-асоційованою змішаною кріоглобулінемією (90,3 %). Наявність у хворих на ХГС зі змішаною кріоглобулінемією генотипів CG/GG асоційована з вираженішими імунологічними порушеннями внаслідок найвищого вмісту ІЛ-6, змішаних кріоглобулінів, RF IgM у сироватці крові, що зумовлює маніфестацію клінічної симптоматики цього позапечінкового прояву. Цель работы – определить роль взаимосвязи иммунологических нарушений с полиморфизмом гена интерлейкина-6 в формировании HCV-ассоциированной смешанной криоглобулинемии. Материалы и методы. В исследование включили 149 пациентов с хроническим гепатитом С (ХГС). Определен полиморфизм гена ИЛ-6 (rs1800795) методом полимеразной цепной реакции, количественное содержание ИЛ-6, RFIgM и IgG методом иммуноферментного анализа, а также криоглобулины спектрофотометрическим методом. Пациенты разделены на группы в зависимости от полиморфизма гена ИЛ-6 и наличия смешанной криоглобулинемии. Результаты. Установлено, что частота формирования HCV-ассоциированной смешанной криоглобулинемии зависела от полиморфизма гена ИЛ-6. У больных ХГС со смешанной криоглобулинемией частота регистрации генотипа СС гена ИЛ-6 была ниже, чем у пациентов без смешанной криоглобулинемии – у 9,7 % против 28,6 % больных. Наличие G-аллели, а именно генотипов CG/GG полиморфизма гена ИЛ-6 чаще установлено у больных со смешанной криоглобулинемией – у 90,3 % против 71,4 % больных без признаков смешанной криоглобулинемии (χ2 = 8,94, р = 0,003). При наличии G-аллели количественное содержание ИЛ-6 в сыворотке крови общей группы больных ХГС было выше, чем у здоровых людей (р < 0,01), а при наличии генотипа СС не отличался от показателей лиц контрольной группы (р > 0,05). Самый высокий уровень содержания ИЛ-6 зафиксирован у пациентов с HCV-ассоциированной смешанной криоглобулинемией, у которых была G-аллель. Содержание ИЛ-6 в сыворотке крови этих больных превышал показатели как здоровых людей (р < 0,001), так и пациентов без смешанной криоглобулинемии (р < 0,01). У больных ХГС со смешанной криоглобулинемией даже при наличии СС-генотипа содержание ИЛ-6 в сыворотке крови было выше в сравнении и со здоровыми (р < 0,01), и больными без признаков этого внепеченочного проявления (р < 0,01). У больных ХГС со смешанной криоглобулинемией наличие генотипов CG/GG ассоциировалось не только с самым высоким содержанием ИЛ-6 в сыворотке крови, но и с наличием более выраженных аутоиммунных нарушений за счет более высокого содержания RF IgM (р = 0,04) и смешанных криоглобулинов (р = 0,03) в сыворотке крови в сравнении с пациентами, которые имели генотип СС. Наличие более выраженных иммунных нарушений у больных с HCV-ассоциированной смешанной криоглобулинемией при наличии генотипов CG/GG сопровождалось более частой манифестацией выраженной общей слабости (р = 0,003), артралгий (р = 0,02) и формированием триады Мельцера. Выводы. Частота установления G-аллели, а именно генотипов CG/GG полиморфизма гена ИЛ-6, самая высокая у больных с HCV-ассоциированной смешанной криоглобулинемией (90,3 %). Наличие у больных ХГС со смешанной криоглобулинемией генотипов CG/GG способствует более выраженным иммунологическим нарушениям за счет самого высокого содержания ИЛ-6, смешанных криоглобулинов, RF IgM в сыворотке крови, что обусловливает манифестацию клинической симптоматики этого непеченочного проявления.
Взаємозв’язки імунологічних порушень із поліморфізмом гена інтерлейкіну-6 та їхня роль у формуванні HCV-асоційованої змішаної кріоглобулінемії у хворих хронічним гепатитом С
Взаимосвязи полиморфизма гена интерлейкина-6 с иммунологическими нарушениями и их роль в развитии смешанной криоглобулинемии у больных хроническим гепатитом С
Keywords: chronic hepatitis C; mixed cryoglobulinemia; interleukin-6; genetic polymorphism; хронічний гепатит С; змішана кріоглобулінемія; інтерлейкін-6; поліморфізм генетичний; хронический гепатит С; смешанная криоглобулинемия; интерлейкин-6; полиморфизм генетический